Penggunaan Bahasa Cina dalam weblog di Malaysia / Teoh Jun Yong - Teoh, Jun Yong (2012)
The development of weblog in virtual world has progressed so rapidly that it has influenced the different aspects of languages. The use of such language in our daily life has caused various styles of language such as the internet Chinese language to evolve. This research is carried out to identify and analyse the characteristics of the internet Chinese language on weblog among the youth in our country. Besides, researcher will also discuss the factors involved in the existence of the internet Chinese language on weblog through the views of these youth. As many as 40 weblogs have been collected as sample study. Only personal weblogs are chosen in Chinese which have been presented on the internet from January to December 2008 are used in this study. This sample study is analysed both qualitatively and quantitatively. There are six aspects of linguistic like code mixing, code switching, acronym, vulgar language, repeated and ghafalogical. From the study, researcher had found that most of the local blogger prefer using code mixing which include the use of Bahasa Melayu and English. In addition, it is found that the use of emoticons, punctuation, ellipsis, fonts and colour are very common among them. Feedback from respoundents shows that the blogger’s hidden identities a main factor in creating new lexical items. The study concludes that a neutral attitude should be adopted in view of the fact that the number of such users are steadily increasing